1995
DOI: 10.1108/00070709510104303
|View full text |Cite
|
Sign up to set email alerts
|

Who buys organic food?

Abstract: Foster, (2005),"Exploring the gap between attitudes and behaviour: Understanding why consumers buy or do not buy organic food", If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(89 citation statements)
references
References 10 publications
(6 reference statements)
6
61
1
5
Order By: Relevance
“…The pattern of world food consumption has changed over the last two decades towards a greater demand for quality attributes. Among the reasons for this shift are: concern for health and nutrition (Tregear, Dent & McGregor, 1994), eroded confidence in the conventional food industry (Alvensleben & Attmann, 1987), concern for the environment (Wandel & Bugge, 1997), concern with the chemicals in conventional food products (Dixon & Holmes, 1987), improved taste and flavour of organics products (Davies, Titterington & Cochrane, 1995;Feber et al1998), and animal welfare (Hutchins & Greenhalgh, 1997). Organic farming has been the subject of debate, as it goes to the heart of the issue of whether incentives and technical support for organic sector expansion are needed and even whether widespread organic agriculture would be capable of producing sufficient food (Francis and van Wart, 2009;Avery & Avery, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of world food consumption has changed over the last two decades towards a greater demand for quality attributes. Among the reasons for this shift are: concern for health and nutrition (Tregear, Dent & McGregor, 1994), eroded confidence in the conventional food industry (Alvensleben & Attmann, 1987), concern for the environment (Wandel & Bugge, 1997), concern with the chemicals in conventional food products (Dixon & Holmes, 1987), improved taste and flavour of organics products (Davies, Titterington & Cochrane, 1995;Feber et al1998), and animal welfare (Hutchins & Greenhalgh, 1997). Organic farming has been the subject of debate, as it goes to the heart of the issue of whether incentives and technical support for organic sector expansion are needed and even whether widespread organic agriculture would be capable of producing sufficient food (Francis and van Wart, 2009;Avery & Avery, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing understanding of consumers' attitudes and their responses to green restaurants is the aim of this research. A number of researches have focused on green consumers' purchases of sustainable food, such as green food, organic food, eco-friendly food [6,15]. There are some researchers focused on the relationship between consumer attitude and behavior in response to green products [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on consumers' purchases of organic and eco-friendly food (e.g., [6,15]). Indeed, environmental concern is often used to measure the importance of the environment and its protection and has been cited as an indicator of the "greening" of consumption [21].…”
Section: Introductionmentioning
confidence: 99%
“…Byrne, Toensmeyer, German, & Muller (1991), Davies, Titterington, & Cochrane (1995), and Ahmad and Juhdi (2008) indicated that when there is a lack of organic food and green products availability in stores, it could be considered as a major obstacle that consumers could face during their purchasing process. Availability means the level of difficult or ease to find or to consume a specific product.…”
Section: Timementioning
confidence: 99%